2011
DOI: 10.1371/journal.pone.0017416
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Organization of Proton and Lactate Transport in a Rat Brain Tumor

Abstract: Tumors create a heterogeneous acidic microenvironment which assists their growth and which must be taken into account in the design of drugs and their delivery. In addition, the acidic extracellular pH (pHe) is itself exploited in several experimental techniques for drug delivery. The way the acidity is created is not clear. We report here the spatial organization of key proton-handling proteins in C6 gliomas in rat brain. The mean profiles across the tumor rim of the Na+/H+ exchanger NHE1, and the lactate-H+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 71 publications
5
49
3
Order By: Relevance
“…Similar lactate exchange and uptake through MCT1 is reported in the heart (8), red blood cells (9), and even in the liver, to support gluconeogenesis (10). Within tumors also, we and others recently documented that cancer cells could import lactate through MCT1 from the most glycolytic tumor cells (11)(12)(13)(14) or tumor-associated fibroblasts (15,16) to fuel mitochondrial respiration and thereby spare glucose for hypoxic tumor cells. In many tumor cell lines, characterized by an elevated glycolytic flux even in the presence of oxygen (the Warburg effect; ref.…”
Section: Introductionsupporting
confidence: 53%
“…Similar lactate exchange and uptake through MCT1 is reported in the heart (8), red blood cells (9), and even in the liver, to support gluconeogenesis (10). Within tumors also, we and others recently documented that cancer cells could import lactate through MCT1 from the most glycolytic tumor cells (11)(12)(13)(14) or tumor-associated fibroblasts (15,16) to fuel mitochondrial respiration and thereby spare glucose for hypoxic tumor cells. In many tumor cell lines, characterized by an elevated glycolytic flux even in the presence of oxygen (the Warburg effect; ref.…”
Section: Introductionsupporting
confidence: 53%
“…An acidic extracellular milieu favors tumor growth, invasion, and development (15)(16)(17)(18)(19)(20), and the pHLIP peptides can exploit tumor acidity as a useful biomarker. Based on the results of our previous and current investigations, design principles can be formulated to set directions for different clinical uses:…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to increase pH i , suggesting that anoxic cells at a tumor center can have a higher pH i than peripheral cells. However, a recent study of rat brain gliomas found that NHE1 and MCT1 are more abundant at the tumor edge (Grillon et al, 2011), although pH i was not determined. Furthermore, increased pH i has recently been proposed to be necessary for epithelial-to-mesenchymal transition (Amith et al, 2016b), and epithelial-to-mesenchymal transition is implicated in initiating metastasis.…”
Section: Tumorigenesismentioning
confidence: 94%